Tuning the hybridization and charge polarization in metal nanoparticles dispersed over Schiff base functionalized SBA-15 enhances CO2 capture and conversion to formic acid - Cherevotan, Arjun; Ray, Bitan; Yadav, Anish; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Churipard, Sathyapal R.; Naral, Vinay; Kaur, Komalpreet; Gautam, Ujjal K.; Vinod, Chathakudath P.; Peter, Sebastian C. (Journal of Materials Chemistry A, 2022)
Different Schiff base functionalized SBA-15 materials were synthesized through condensation reactions between 3-aminopropyltriethoxysilane (APTES) and different aldehydes (glutaraldehyde and butyraldehyde) over a mesoporous silica, SBA-15 (APTES-GLU/SBA-15 and APTES-BUT/SBA-15). Both static and dynamic experiments have been used for testing the CO2 capture efficiency of these materials. The hybridization of the N atom in APTES has been tuned from sp(3) to sp(2) upon condensation facilitating optimum CO2 capture in the direct synthesis of APTES-GLU/SBA-15. The undesirable oxides of nitrogen have been removed during the synthesis process to improve the CO2 capture efficiency. These materials were employed as supports for Pd-Ag and Pd-Ni bimetallic systems for the selective conversion of the captured CO2 to formic acid (FA) in 0.5 M KHCO3 solution. The Pd-Ni catalyst system exhibited enhanced CO2 to FA conversion activity compared to other heterogeneous systems, which is similar to 4 times better than that of the Pd-Ag system in this study. The X-ray absorption studies over the catalyst material confirmed that the relatively electron-deficient Ni in Pd-Ni compared to Ag in Pd-Ag favoured higher charge polarization between the metals in the Pd-Ni system enhancing the CO2 to FA conversion. The experimental observations are well supported by the DFT calculations.

Towards improved activity and stability in RWGS reaction: Dispersed copper in mesoporous alumina matrix as a strategy for enhanced performance - Saju, Simi; Rajendran, Sivaraj; Oztas, Ulviye; Ruiz, Sergio Carrasco; Reina, Tomas Ramirez; Ghosh, Biplab; Sree, Sreeprasanth Pulinthanathu; Meena, Raghavendra; Li, Guanna; Bobadilla, Luis F.; Vinod, Chathakudath P.; Mathew, Thomas; et al. (Chemical Engineering Journal, 2025)
The development of highly performing Cu-based catalysts with high dispersion of Cu species in nanocrystalline form on a suitable oxide support is significant in reverse water gas shift (RWGS) reaction. We report a simple and robust one-pot sol-gel synthesis of mesoporous Al10-xCuxOy (m gamma-Al10-xCux-SG) catalysts with Cu species in a highly dispersed nanocrystalline form in the gamma-Al2O3 matrix and its high catalytic performance in RWGS reaction. The lack of long range structural order of copper species in m gamma-Al10-xCux-SG catalysts evidenced from Cu-K edge extended X-ray absorption fine structure (EXAFS) studies illustrates the fine distribution of copper species in mesoporous gamma-Al2O3 lattice. Activity study revealed that m gamma-Al10-xCux-SG catalysts showed significantly high CO2 conversion to CO and excellent catalytic stability compared to gamma-Al10-xCux-I prepared by conventional impregnation method. Mesoporous Al9Cu1 (m gamma-Al9Cu1) displayed a CO2 conversion of 45 % at 500 degrees C, which is about 2.8 times higher activity than conventional gamma-Al9Cu1-I catalyst with almost same Cu loading as that of m gamma-Al9Cu1 catalyst. Stability study at 500 degrees C over a period of 50 h revealed that m gamma-Al10-xCux-SG catalysts at low Cu loading (m gamma-Al9.9Cu0.1) showed excellent catalytic stability. The strong copper-alumina interaction in m gamma-Al10-xCux-SG catalysts with enhanced number of active sites at the copper-alumina interface as evidenced from field emission scanning electron microscope (FESEM), high-resolution transmission electron microscope (HRTEM), H2-temperature programmed reduction (H2-TPR), X-ray photoelectron spectroscopy (XPS), electrochemical characterization, and Cu-K edge EXAFS analysis enhances the activity and stability of the catalyst. Density functional theory (DFT) studies and the Operando DRIFTS-MS analysis of RWGS over m gamma-Al9Cu1 catalyst revealed that the mechanism of RWGS reaction to CO formation on m gamma-Al10-xCux-SG catalysts is preceded through the formation of a hydroxycarbonyl (OCOH) intermediate. The present synthesis strategy provides an opportunity for producing Cu-based catalysts with further enhanced activity and stability in RWGS reaction by suitable modification of the catalyst.